2014
DOI: 10.12957/reuerj.2014.4516
|View full text |Cite
|
Sign up to set email alerts
|

Uso de álcool e condições de saúde de motoristas de caminhão

Abstract: RESUMO: O estudo teve por objetivo identificar o uso do álcool e as condições de saúde de motoristas de caminhão participantes de uma campanha de saúde. O desenho metodológico é do tipo descritivo, na abordagem quantitativa. A coleta de dados foi realizada, entre agosto e outubro de 2006, em uma rodovia do interior paulista, por meio de um questionário contendo informações sociodemográficas, Teste de Identificação do Uso de Álcool (AUDIT) e informações sobre condições de saúde. De 1087 participantes, 827 eram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…There are a lot of articles about alcohol, tobacco and illicit drugs consumption in groups of truck drivers through questionnaires across the country (Oliveira et al, 2013;Berti et al, 2013;Takitane et al, 2013;Domingos et al, 2014, Oliveira et al, 2016, Pereira et al, 2021, Scherer et al, 2021. However, this one is the first study that estimated the prevalence of these drugs through a questionnaire validated by the World Health Organization (WHO), as well as the initiative to list the intervention procedures and/or treatment to be used in participants who do consume abuse of licit and illicit substances.…”
Section: Discussionmentioning
confidence: 99%
“…There are a lot of articles about alcohol, tobacco and illicit drugs consumption in groups of truck drivers through questionnaires across the country (Oliveira et al, 2013;Berti et al, 2013;Takitane et al, 2013;Domingos et al, 2014, Oliveira et al, 2016, Pereira et al, 2021, Scherer et al, 2021. However, this one is the first study that estimated the prevalence of these drugs through a questionnaire validated by the World Health Organization (WHO), as well as the initiative to list the intervention procedures and/or treatment to be used in participants who do consume abuse of licit and illicit substances.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is in the smooth endoplasmic reticulum of hepatocytes and uses cytochrome P-450, NADPH-cytochrome reductase, and phospholipids, having as hydrogen acceptor NADP (Scheme A of Figure 2). However, in this pathway, there is energy expenditure in the form of ATP and use of oxygen and NADPH (nicotinamide adenine dinucleotide phosphate) in its reduced form, not generating energy-forming components such as NADH [1,8,16]. Another pathway used in heavy drinkers and chronic alcoholics is the catalase pathway (Diagram C of Figure 2), which has small participation in the process since it metabolizes only 10% of the alcohol ingested.…”
Section: Alcohol Metabolism and Weight Gainmentioning
confidence: 99%
“…Scholars debate that the energy consumed in alcohol is additive to other dietary sources and that the increase in energy intake with the consumption of alcoholic substances can probably promote a positive energy balance and thus favor weight gain [4][5][6][7][8][9][10][11][12] A study by Yeomans [6], which investigated alcohol intake as a risk factor for the development of obesity, found that the analyzed research showed that the energy consumed in the form of alcohol is additive to that of other dietary sources, leading to excess short-term passive energy consumption. Alcohol consumed before or with meals tends to increase food intake, probably by increasing the short-term rewarding effects of food.…”
Section: Introductionmentioning
confidence: 99%